3D evaluation of tooth crown size in unilateral cleft lip and palate patients - Kaplan, M.; Görgülü, Sinan; Cesur, Emre; Arslan, Can; Altuğ, Ayşe Tuba (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this retrospective study is to evaluate and compare the 3-dimensional (3D) crown sizes of the left and right sides of upper and lower dental arches in patients with unilateral cleft lip and palate (UCLP). Materials and Methods: Dental casts of 94 patients all in permanent dentition were included in this study. Dental casts were divided into three groups as 36 casts with unilateral left cleft lip and palate (ULCLP), 18 casts with unilateral right cleft lip and palate (URCLP), and 40 casts without cleft (control). Mesiodistal (MD), buccolingual (BL), and gingiva incisal (GI) values of each tooth were measured by scanning the dental models with a high-precision optical 3D scanner. Paired t-test and independent t-test were used for statistical analysis. Results: U1 MD, U6 MD (P = 0.001) and BL (P = 0.01), L3 GI (P = 0.05) were greater in UCLP patients on the non-cleft side while U1 GI, L1 BL, L5 MD (P = 0.001), L4 MD, and BL (P = 0.01) values were found to be greater on the cleft side. Comparison of the cleft-sides and the control group showed that MD, BL, and GI dimensions of teeth on the cleft sides were generally found to be smaller, excluding the UR7 GI values for URCLP group (P = 0.05). Conclusion: In the measurements of teeth size, reliable and repeatable results were acquired through 3D software. Tooth size asymmetries can occur non-syndromic UCLP patients in both jaws. MD, BL, and GI dimensions of teeth are mostly found to be smaller in patients with CLP.
Keywords: 3D; Cleft Lip and Palate; Crown Size; Tooth Size